2020
DOI: 10.1002/ccr3.3030
|View full text |Cite
|
Sign up to set email alerts
|

Novel approach for peptic ulcer perforation surgery

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Questions related to the management of a PUP were as follows [ 1 ]: Is surgery indicated? [ 2 ] Is an omental patch indicated as sufficient for ulcer operation ? [ 3 ] Is the patient able enough to undergo surgery?…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Questions related to the management of a PUP were as follows [ 1 ]: Is surgery indicated? [ 2 ] Is an omental patch indicated as sufficient for ulcer operation ? [ 3 ] Is the patient able enough to undergo surgery?…”
Section: Discussionmentioning
confidence: 99%
“…However, the omentum of thin or elderly patients may be very attenuated or virtually non-existent. However, in some select patients where the greater omentum is either unviable, unhealthy, or cannot be utilized, the falciform ligament can be used as an adequate patch for closure [ 2 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve studies reported use of falciform ligament in gastrointestinal surgery with most common technique employing falciform ligament in perforated gastric or intestinal ulcer as an alternative to graham patch. 1,[6][7][8][9][10][11] A total of 14 patients underwent falciform ligament for intestinal perforation. No mortalities were reported, and no studies reported technical complications or unplanned returns to the operating room.…”
Section: Gastrointestinal Surgerymentioning
confidence: 99%